Functional Analysis of Hedges and Boosters in Academic Students Essays: Across Disciplinary Study - آزاده ملاکی; سید فواد ابراهیمی; محمد تقی فروردین (Journal of Applied Linguistics)
Hedging and boosting are significant communicative resources to construe and attain persuasion in different fields and particular genres of academic writing. Hedges allow the researcher to address possible problems, raise objections or anticipate opposition to the research claims while contributing something new to the ongoing dialogue in a research field. Boosters enormously help to achieve the essential writers’ need to convince their readership of the truth in their propositions. They are mainly used whenever writers consider it not too risky to include them in their propositions. This study aims to investigate the frequencies and functions of hedges and boosters in academic students' essays. To meet this end, 96 students' essays (a total of 269.428 words) were selected from the Michigan Corpus of Upper-Level Student Papers (MICUSP), including English and Psychology disciplines. The corpus was analyzed based on Abdollahzadeh (2019)classification of hedges. The results showed that hedges and boosters were frequent enough to be considered in teaching writing, either reducing or increasing the force of written utterances. The results of this study could be used directly in the syllabus designed for academic essay writing.